Penggunaan Analisis SWOT dalam Mengembangkan Po-tensi Usaha Dodol Nenas Kelompok Tani Tunas Makmur Sungai Pakning - Wan Junita Raflah (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to find out potential development strategy of pineapple dodol business of Tunas Makmur farmer grpup in sungai Pakning using SWOT analysis. This study was conducted in Kampung Jawa Sungai Pakning using primary and secondary data in which primary data was collected through interviews, observations and literature review. The result of this study found that the strategy for developing the pineapple dodol business in Tunas Makmur Sungai Pakning is to implement an aggressive strategy by increasing the amount of pineapple production, maintain the good quality product, Product innovation, penetrate foreign markets, Increase partnerships, especially in the fields of marketing, technology and capital.